Pengaruh Pelatihan Perawatan Tali Pusat dengan Metode Simulasi terhadap Keterampilan Merawat Tali Pusat pada Ibu Primigravida Trimester II-III di Wilayah Kerja Puskesmas Ledokombo Kabupaten Jember (The Influence of Umbilical Cord Care Training (UCCT) by S - Rosalind Prihandini; Ratna Sari Hardiani; Rondhianto Rondhianto (Pustaka Kesehatan, 2015)
Umbilical cord care is a treatment of newborn baby’s umbilical cord started when umbilical cord was cut off or dried up. A well took umbilical cord care allow baby to heal faster. Umbilical Cord Care Training (UCCT) by simulation method aims to provide skill in performing umbilical cord care of primigravida in preventing infections and tetanus neonatorum. This research was intended to analyze the influence of UCCT to umbilical cord caring skill of 2nd and 3rd trimester primigravida. This was a quasy experimental study with non-randomized control group and pretest-posttest design. The samples were 32 primigravide picked out by multistage random sampling and divided into two groups. Data were analyzed by Wilcoxon match pair test and Mann Whitney U test with 95% of CI. The result showed p value of Wilcoxon match pair test in experimental group was 0,000 and 1,000 in control group, while by Mann Whitney obtained p value of 0,000 (a=0,05). It can be concluded that there was an influence of UCCT to primigravida’s skill in performing umbilical cord care. Hereby, suggested to nurses to give UCCT by simulation method at maternal and child health center to prepare primigravida on caring newborn baby to prevent infections and tetanus   Keywords: umbilical cord care training, simulation method, skill